Analisis Kinerja Keuangan pada Sub Sektor Farmasi yang Terdaftar di Bursa Efek Indonesia Menggunakan Metode Economic Value Added dan Market Value Added - Putri, Avirdha; Chazan Azari; Winarto (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2023)
The pharmaceutical industry experienced growth from 2019 to 2021, driven by increased demand for medicines. However, in 2022, the growth of the pharmaceutical industry slowed down due to the impact of the Covid-19 pandemic in Indonesia. This research aims to describe the financial performance conditions of pharmaceutical sub-sector companies, measured using the Economic Value Added (EVA) and Market Value Added (MVA) methods. The research method used is a quantitative method with a descriptive approach. The type of data used is secondary data obtained from the website www.idx.co.id. The sample selection was carried out using purposive sampling technique, resulting in a total of 10 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (BEI) during the period from 2019 to 2022. The results of the financial performance analysis of companies using the EVA method indicate that pharmaceutical sub-sector companies have a good performance as they were able to generate a positive Economic Value Added (EVA > 0), signifying that the companies generated profits greater than the cost of capital, thus indicating good financial performance. Meanwhile, the financial performance analysis using the MVA method shows that pharmaceutical sub-sector companies were able to produce a positive Market Value Added (MVA > 0), indicating that the performance of the pharmaceutical sub-sector is in a good condition as the market value of the companies experienced an increase that exceeds the total capital invested by shareholders.